2014
DOI: 10.5846/stxb201312022869
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of reference crop evapotranspiration and its influencing factors in the North China Plain

Abstract: Potential evapotranspiration is the theoretical upper limit value of actual evapotranspiration, which constitutes the important parameters for the research of regional thermal balance, water budget, water resources assessment and crop water requirements. Study on regional response of potential evapotranspiration to global climatic changes in China has significance in global hydrological cycling, energy balance and eco鄄environmental evolution research. Reference crop evapotranspiration (ET 0) as a common parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Mean yield in 2013-2014 was 6% higher than in the second, 2014-2015, suggesting that WP may vary by this amount regardless of irrigation schedule and quantity. The underlying reason for this result was that sunshine hours and wind speed were different in the 2 years, dominant factors that caused change of ET 0 in the North China Plain (Wang et al, 2014). The sunshine hours in second year (2580 h from October 2014 to September 2015) were significantly higher than those in the first year (2335 h).…”
Section: Discussionmentioning
confidence: 90%
“…Mean yield in 2013-2014 was 6% higher than in the second, 2014-2015, suggesting that WP may vary by this amount regardless of irrigation schedule and quantity. The underlying reason for this result was that sunshine hours and wind speed were different in the 2 years, dominant factors that caused change of ET 0 in the North China Plain (Wang et al, 2014). The sunshine hours in second year (2580 h from October 2014 to September 2015) were significantly higher than those in the first year (2335 h).…”
Section: Discussionmentioning
confidence: 90%
“…Annual ET 0 in Guangdong is slightly increasing at a rate of 2.76 mm/10a; it appears that many regions around the globe significantly influenced by oceanic climate recorded an increasing trend in ET 0 , such as the Korean Peninsula, which is in a subtropical monsoon climate zone [43]; Paraíba, Brazil, and Madagascar, which are in tropical high-temperature climate zones [44]; and Austria, which is in a maritime temperate broad-leaved forest climate zone [45]. This trend is different from those recorded in other regions in China, such as the Yellow River Basin [46], North China Plain [47], Northwest China [36], and Beijing-Tianjin-Hebei regions [48], where ET 0 decreased since the 1960s, creating an "evap-oration paradox". This paradox exists at about 62% of the stations across China, where ET 0 decreases at a rate of 5.2 mm/10a despite an increase in temperature [14].…”
Section: Changing Trends Of Meteorological Factors and Et0mentioning
confidence: 92%
“…Meng et al [9] discovered that large interannual differences in maize evapotranspiration in the black soil region of Northeastern China are mainly due to monsoon climate. According to Wang et al [10], the dominant meteorological factors affecting evapotranspiration in the North China Plain are sunshine hours and wind speed, while relative humidity and temperature have less impact. Jiang et al [11] found that the main meteorological factors affecting summer maize evapotranspiration in Xinjiang in 2015 were net radiation and relative humidity.…”
Section: Introductionmentioning
confidence: 99%